The political discourse of the Peruvian emigrants in Chile: El Intérprete, 1836-1837 - Puerta Villagaray, César (2018)
The objective of the article is to study the political discourse elaborated by the Peruvian emigres in Chile between 1836 and 1837. The aim is to understand how the emigrants justified their struggle against the Peru-Bolivia Confederation and the support they offered to the intervention Chilean military. In this sense, it is argued that the discourse of the Peruvian emigrants was part of a political struggle, in which two republican ideals coexisted in permanent tension: the civic patriotic and the nationalist.